Design and sustainability for innovation in family firms. A case study from the italian furniture sector - Barbaritano, Marica; Savelli, Elisabetta (Piccola Impresa / Small Business, 2020)
The increasingly competitive environment requires a continuous innovation for both firms’ survival and competitiveness, particularly for family firms. The focus of this study is on the furniture sector and it aims to investigate to what extent circular economy and sustainability practices can be considered as tools for design innovation. The case of an Italian manufacturing firm has been deeply analysed. Notably, by investigating a recent innovation carried out within the company, the study provides empirical evidence that sustainability can be actually considered as an innovative force generating new products and processes.